PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS MULTI REPRESENTASI TERHADAP PEMAHAMAN KONSEP SISWA - Yusi Martiasari; Zaenal Abidin; Lilis Lismaya (Quagga : Jurnal Pendidikan dan Biologi, 2016)
This research is conducted to know the influence of application of problem based learning model multi representative-based toward students’ understanding concept, to know the difference of posttest result between experiment class and control class, to know students’ respond toward learning that applied problem based learning model multi representative-based. This research is conducted at SMAN 1 GARAWANGI for five meetings with quasi experiment method that used Pretest and Posttest Control Group Design. Technique of taking samples used Cluster Random Sampling, 63 students of IX class were divided into experiment class and control class. In experiment class, students were taught with Problem Based Learning Model Multi Representative-Based, meanwhile students in control class were taught with Problem Based Learning Model. The collected data was analyzed with T test. The result of this research shows that t count t table, that is 2,86 2,66. The average score in experiment class is 62,97 while in control class is 52,37. From that result, it can be concluded that application of Problem Based Learning Model Multi Representative-Based is influential toward students’ understanding concept. Key Word : Problem Based Learning, Multi Representative, Understanding Concept